SYSTEMATIC LITERATURE REVIEW (SLR): PERUBAHAN PERAN CHIEF FINANCIAL OFFICER (CFO) DALAM MENGOPTIMALKAN PENGGUNAAN TEKNOLOGI, DAN KETEPATAN ALAM PENGAMBILAN KEPUTUSAN STRATEGIS - Usman, Asri; Mediaty, Mediaty; Pitria, Ni Gusti Ayu; Nurfadilah, Ayu; Nurazisah, Andi Fadhilah (Universitas Nusa Cendana, 2024)
This research aims to review the CFO's role's evolution and technology's impact on the modern CFO function. The study uses a Systematic Literature Review (SLR) to investigate the Chief Financial Officer's (CFO) changing role in optimizing the use of the latest technology and process automation. The SLR findings indicate the CFO's role has shifted from a technical finance role to a business leader providing strategic recommendations and financial risk analysis. The research found that by utilizing the latest technology, CFOs can optimize operational efficiency and support faster, more accurate business decision-making. Based on upper echelon theory, the CFO's characteristics affect the company's decisions. Therefore, companies should consider CFOs' experience and education in supporting their strategic role. The study's originality lies in discussing the CFO's role development in the digital era and the impact of the latest technology on strategic decision-making. Keywords: Chief Financial Officer; Use of Technology; Operational Efficiency; Decision Making